Pelaksanaan Program Sekolah Pra Nikah pada Remaja dalam Mencegah Angka Stunting di Wilayah Kecamatan Sawangan - Muhammmad Salman Al Farizi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Stunting is one of the challenges in human development in Indonesia, referring to the condition of failure in physical growth in children under five years old due to chronic malnutrition and repeated infections, particularly during the first 1,000 days of life, from conception until the child is 23 months old. The Pre-Marriage School (SPN) program by DP3AP2KB in collaboration with the Forum Generasi Berencana (GENRE) serves as an educational platform focused on preparing for marriage and life after marriage with proper planning. The goal of the pre-marriage school is to educate participants on the importance of stunting awareness. The SPN program is part of the efforts by DP3AP2KB to prevent stunting by providing education related to the condition. This research employed qualitative methods with a descriptive qualitative approach, using interviews and documentation for data collection. The study subjects were participants of the pre-marriage school who met the research criteria. Data were analyzed using the Milles & Huberman model, ensuring data validity through method triangulation. The study found that the causes of stunting in Depok City included inadequate nutrition, poor parenting practices, and urbanization. The implementation of the pre-marriage school program in Depok City was designed by the DPRD Commission V and the Mayor of Depok. The pre-marriage school is one of the government’s efforts to accelerate the reduction of stunting in Depok City. However, the limited time for implementation posed a challenge for the SPN program